The significance of Martin Buber’s philosophy of dialogue and suffering in the overcoming of ‘core-to-core confrontation’ in Chaim Potok’s The Chosen - Sánchez Canales, Gustavo (Estudios Ingleses de la Universidad Complutense, 2010)
One of the central issues in Chaim Potok’s works is what he calls ‘core-to-core [culture] confrontation’, that is to say the clash between the core of an individual’s world and the core of another wider world. Specifically, in The Chosen (1967), this confrontation occurs when the core of Danny Saunder’s worldthe son of an ultra-conservative Hasidic leader called Reb Saunderscollides with the core of a more general world in which he livesWestern secular culture. This clash, which results in the confrontation of Reb Saunders and Danny, is largely due to the Reb’s opposition to his son’s wish to study psychoanalysis. In this article, I will focus on how Martin Buber’s philosophy of dialogue facilitates the mutual understanding between two opposing worlds in The Chosen. The conflict is finally resolved when, using Buber’s terms, the characters’ relationships move from an ‘I-It’ to an ‘I-Thou’ relationship. This process of coming to terms with each other inevitably brings about much suffering on Potok’s characters’ part. In the second part of the present article, I will try to show how suffering can transform them into more sympathetic human beings.